Bahilah di Hulu Sungai Utara: Penebus Dosa Ala Urang Amuntai - Siti Muna Hayati; Husnul Khitam (LP2M IAIN Palangka Raya, 2018)
This study is aimed at examining the Bahilah custom facing a shift in practice and how the views of North Hulu Sungai society towards the Bahilah custom. This study belongs to descriptive qualitative research using observation and interview methods. The study reveals that some modern societies and living in urban areas consider the bahilah custom not based from the Nash (Qur’anic text) and violate the rules in religion. Therefore, they ignore it. Meanwhile, some of the traditionalist societies practicing Syafii School regard the Bahilah custom as something that is forbidden. Despite of the existing debate, the people majority of Amuntai City in the North Hulu Sungai Regency who in fact follow the Shafi'i school have always carried it out until now when their relatives died. In fact, the problems arising later are not about the validity of the argument, but with regard to the amount of costs that must be incurred because of the shifting essence and the Bahilah practice that has always been carried out.